Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens. Issue 10 (18th May 2016) - Wang, Tao; Wu, Mian-Bin; Chen, Zheng-Jie; Lin, Jian-Pin; Yang, Li-Rong
Abstract : A new Bacillus amyloliquefaciens named ZJU-2011 was discovered, and the culture supernatant showed a strong inhibitory effect against Candida albicans . In this study, a novel method was developed to purify the antifungal compounds in high purity. The obtained products were analysed by high performance liquid chromatography and proven to be of high purity. Mass spectrometry showed that the molecular weights of the two bioactive components were 270 and 288, respectively, and their structures were determined to be bacilysin and chlorotetaine by using 1 H and 13 C nuclear magnetic resonance spectroscopy. To the best of our knowledge, this is the first time that B. amyloliquefaciens has been reported to produce bacilysin and chlorotetaine simultaneously. The minimum inhibitory concentration of chlorotetaine against six common fungal pathogens were determined to be in the range of 1.8–7.8 μg/mL. Abstract : Flow chart of the process of separation and purification of bacilysin and chlorotetaine.